MP3: Medical Software for Processing Multi-Parametric Images Pipelines - Brossard, Clément; Montigon, Olivier; Boux, Fabien; Delphin, Aurélien; Christen, Thomas; Barbier, Emmanuel L.; Lemasson, Benjamin (Frontiers in Neuroinformatics, 2020)
This article presents an open source software able to convert, display and process medical images. It differentiates itself from the existing software by its ability to design complex processing pipelines and to wisely execute them on a large database. An MP3 pipeline can contain unlimited homemade or ready-made processes and can be carried out with a parallel execution system. As a viewer, MP3 allows to display up to 4 images together and to draw Regions Of Interest (ROI). Two applications showing the strengths of the software are here exposed: a preclinical study involving Magnetic Resonance Imaging (MRI) data and a clinical one involving Computed Tomography (CT) images. MP3 is downloadable at https://github.com/nifm-gin/MP3.